SESSION IV: Gender based violence - NINTH NATIONAL CONVENTION ON WOMEN'S STUDIES ( Colombo, 20-23rd March 2004) (Colombo: Centre for Women's Research, 2004)
An article from MWRAF is included
Keywords: WOMEN'S STUDIES- Sri Lanka- Congresses; Prostitution-Sri Lanka; Sexual harassment-Public transportation-Sri Lanka